Guru Sebagai Agen Pembelajaran Analisis Peran dan Tanggung Jawab dalam Mencapai Tujuan Pendidikan Nasional - Moh. Kholilur Rohman; Muh. Lutfi Alghifari; Eka Pujawati; Nadiyah Nadiyah (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
Education is the main pillar in nation building, where teachers play a central role in determining the success of the learning process. However, in the modern era, challenges related to teachers' competence and creativity in managing the classroom and creating a conducive learning climate are still problems that need to be overcome. This study aims to analyze the role, function, and competence of teachers in achieving national education goals through a qualitative approach with the literature review method. Data was collected from accredited journal articles indexed in SINTA, with a publication range of 2020-2024, using the Publish or Perish (POP) tool. The results show that professional teachers need to master the material, teaching methods, and understand the needs of students to create an effective learning environment. In addition, teachers' creativity and innovation in managing the classroom and the integration of technology in learning are key factors in improving the quality of education. However, there is still a gap between theory and practice, especially in the application of character-based learning approaches, Islamic values, and inclusive classroom management. This study recommends the need for teacher training and competency development, especially in the use of technology and varied learning approaches, to create a more conducive and inclusive learning climate.